Social inequality in obesity in an Eastern Mediterranean population: evidence from a national health survey in Cyprus - Quattrocchi, A.; Kolokotroni, O.; Demetriou, C. A.; Mosquera, M. C.; Charalambous, A.; Heraclides, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. We aimed to explore socioeconomic factors associated with obesity among adults and to investigate social inequality in obesity prevalence in Cyprus. Study design. Cross-sectional studyMethods. We conducted a survey among 3,021 Greek-Cypriots aged 25-64 years, collecting self-reported demographics, health behaviors, socioeconomic characteristics and anthropometric measurements. We performed univariable and multivariable (adjusting for demographics and health behaviors) sexspecific Poisson’s regression with robust variance, reporting adjusted prevalence ratios (PRs) and 95% confidence intervals.Results. The prevalence of obesity was 22% among males and 17% among females. According to univariable analyses, higher obesity prevalence was associated with increased age, decreased physical activity and decreased alcohol consumption in both genders. In addition, obesity was associated with refugee status and former smoking in males and with a higher healthy diet score in females. There was a clear linear decrease in obesity prevalence each step up the socioeconomic hierarchy in both genders. In the fully adjusted model, a clear inverse gradient in obesity prevalence by educational attainment was observed in females (p=0.002), while, in males, lower obesity prevalence remained significantly associated with the highest level of family-net income and educational attainment (aPR:0.48; 95% CI:0.27-0.84 and aPR:0.46; 95% CI:0.25-0.84, respectively). Occupational social class was not associated with obesity.Conclusions. This study highlights striking social inequalities in obesity in an Eastern Mediterranean population, which only recently moved from rural living to high levels of development. We recommend that public health interventions should address education - and income-related barriers, as a means of tackling health inequalities.